Unfair Treatment of Criminal Suspects and Systemic Failure in Human Rights Protection within Indonesia’s Criminal Justice System - Anton Prasetyo; Binsar Jon Vic (Yayasan Cendekia Gagayunan Indonesia, 2025)
The protection of human rights for criminal suspects constitutes a fundamental element of a criminal justice system governed by the rule of law and the principle of due process. However, law enforcement practices in Indonesia continue to demonstrate persistent structural deficiencies that result in unequal and unfair treatment of suspects. This study critically examines systemic failures in the protection of suspects’ human rights, particularly concerning the absence of clear statutory limits on investigation periods, the subjective and repetitive extension of detention, the continued use of coercion and torture during investigative examinations, and the limited access to effective legal assistance, especially for vulnerable groups. Employing a normative legal approach, this research analyzes relevant provisions of the Indonesian Criminal Procedure Code, the Human Rights Law, and international human rights instruments ratified by Indonesia, including the International Covenant on Civil and Political Rights and the Convention Against Torture. The findings reveal a significant gap between normative legal guarantees and their practical implementation, which has enabled abuses of authority by law enforcement officials and undermined fundamental rights such as personal liberty, humane treatment, and the right to a fair trial. The study emphasizes the urgent need for comprehensive criminal justice reform through the clarification of investigation time limits, the strengthening of independent oversight mechanisms, and the expansion of accessible legal aid in order to ensure a more transparent, accountable, and human rights–oriented criminal justice system in Indonesia.